Lab Manual to Accompany The Commercial Greenhouse - Boodley, James (Cengage Learning, Inc, 1998)
The definitive book on greenhouse management--from one of the industry's leading authorities. Scientific yet practical, this brand-new edition presents the latest information in every aspect of the field: not only plant growth and development, but also mass-market sales and financing a greenhouse business. The comprehensive text covers such "hot" topics as hydroponics and environmental controls, while over 150 new photographs, figures, and line drawings depict new equipment and methods. Includes the most recent USDA statistical data on domestic and offshore competition